Pengaruh Current Ratio Dan Debt To Asset Ratio Terhadap Net Profit Margin Pada PT United Tractors Tbk Periode Tahun 2012-2023 - Elsa Pratiwi; Riski Dwi Nugroho (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of Current Ratio and Debt to Asset Ratio on Net Profit Margin at PT United Tractors Tbk for the period 2012-2023. This study is a quantitative descriptive analysis study. The population in this study is the Financial Statements at PT United Tractors Tbk. The research sample used is the Company's Balance Sheet and Income Statement. The analysis of this study uses the SPSS Software Version 26 program. The statistical methods used are the Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test), Multiple Linear Regression Analysis, Correlation Coefficient Analysis (R), Determination Coefficient Analysis (R2), Hypothesis Test (T Test and F Test). The results of the Current Ratio variable (X1) show a partial effect on Net Profit Margin, seen from the T Test which shows the calculated tcount of |-2.452| > ttable which is 2.262 and a significance of 0.037 <0.05. The Debt to Asset Ratio (X2) variable shows a partial influence on Net Profit Margin, seen from the calculated tcount |-1.882| < ttable which is 2.262 and a significance of 0.093> 0.05. The simultaneous results show a positive influence of Current Ratio and Debt to Asset Ratio on Net Profit Margin, seen from the results of the F Test which shows Fcount > Ftable which is 4.368> 4.10. The results of the Determination Test show an R Square value of 0.493 which indicates that the influence of Current Ratio and Debt to Asset Ratio on Net Profit Margin at PT United Tractors Tbk for the 2012-2023 period is 49.3% and the remaining 50.7% is influenced by other variables outside this study.